Quality Assessment of Artemether-Lumefantrine Samples and Artemether Injections Sold in the Cape Coast Metropolis - James Prah; Elvis Ofori Ameyaw; Richmond Afoakwah; Patrick Fiawoyife; Ernest Oppong-Danquah; Johnson Nyarko Boampong (Journal of Tropical Medicine, 2016)
Most prescribers and patients in Ghana now opt for the relatively expensive artemether/lumefantrine rather than artesunate-amodiaquine due to undesirable side effects in the treatment of uncomplicated malaria. The study sought to determine the existence of substandard and/or counterfeit artemether-lumefantrine tablets and suspension as well as artemether injection on the market in Cape Coast. Six brands of artemether-lumefantrine tablets, two brands of artemether-lumefantrine suspensions, and two brands of artemether injections were purchased from pharmacies in Cape Coast for the study. The mechanical properties of the tablets were evaluated. The samples were then analyzed for the content of active ingredients using High Performance Liquid Chromatography with a variable wavelength detector. None of the samples was found to be counterfeit. However, the artemether content of the samples was variable (93.22%−104.70% of stated content by manufacturer). The lumefantrine content of the artemether/lumefantrine samples was also variable (98.70%–111.87%). Seven of the artemether-lumefantrine brands passed whilst one failed the International Pharmacopoeia content requirements. All brands of artemether injections sampled met the International Pharmacopoeia content requirement. The presence of a substandard artemether-lumefantrine suspension in the market should alert regulatory bodies to be more vigilant and totally flush out counterfeit and substandard drugs from the Ghanaian market.